Effect of surface cold ablation on shear strength of CFRP adhesively bonded joint after UV laser treatment. (October 2019) - Zhan, Xiaohong; Chen, Shuai; Li, Yun; Wang, Hongen; Yang, Yang
Abstract: Ultraviolet(UV) laser treatment on the surface of the carbon fiber reinforced polymer (CFRP) laminate becomes an effective method to benefit the bonding strength of adhesively bonded joint in aerospace industries. In the present research, homomorphic CFRP laminates with different resin distribution on the surface are bonded into single-lap joints. Their shear strengths are tested to evaluate the effect of surface resin distribution on bonding mechanical performance. The different resin distributions on the surface of CFRP laminate are obtained by UV pulse laser with different laser scanning speeds. The scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) are conducted to analyze the laser treated surfaces and fracture surfaces of tested joints. The experimental results indicate that the residual resin of CFRP surface increases with the increase of scanning speed. Compared with both the reference surface without laser pre-treatment and that with no-residual resin for bonding, the surface with partial residual resin results in an enhancement of the shear strength of bonded joint. Moreover, the shear strength of the reference sample is higher than that bonded by the surface with no-residual resin. The research lays foundation for understanding the relationship between surface resin distribution and bonding strength.